Diagnostic Markers for Vernalization and Photoperiod Loci Improve Genomic Selection for Grain Yield and Spectral Reflectance in Wheat. Issue 1 (1st January 2018) - Mason, R. Esten; Addison, Christopher K.; Babar, Ali; Acuna, Andrea; Lozada, Dennis; Subramanian, Nithya; Arguello, Maria Nelly; Miller, Randall G.; Brown‐Guedira, Gina; Guedira, Mohammed; Johnson, Jerry
ABSTRACT: The objective of this study was to identify quantitative trait loci (QTL) associated with normalized difference vegetation index (NDVI) measured across different growth stages in a wheat ( Triticum aestivum L.) recombinant inbred line (RIL) population and to determine the predictability of NDVI and grain yield (GY) using a genomic selection (GS) approach. The RILs were grown over three seasons in 12 total site‐years and NDVI was measured in seven site‐years. Measurements of NDVI from tillering to physiological maturity showed low to moderate heritability ( h 2 = 0.06–0.68). Positive correlations were observed among NDVI, GY, and biomass, particularly in low‐yielding site‐years. Quantitative trait loci analysis found 18 genomic regions associated with NDVI, with most pleiotropic across multiple growth stages. The QTL were detected near markers for Ppd‐B1, Ppd‐D1, vrn‐A1, and vrn‐B1, with Ppd‐D1 having the largest effect. Multiple QTL models showed that epistatic interactions between Ppd and Vrn loci also significantly influenced NDVI. Genomic selection accuracy ranged from r = −0.10 to 0.54 for NDVI across growth stages. However, the inclusion of Vrn and Ppd loci as fixed effect covariates increased GS accuracy for NDVI and GY in site‐year groupings with the lowest heritability. The highest accuracy for GY ( r = 0.58–0.59) was observed in the site‐year grouping with the highest heritability ( h 2 = 0.85). Overall, these results will aid in future selection of optimal plant growth for target environments using both phenotypic and GS approaches.